ANALISIS PELUANG DAN TANTANGAN INDUSTRI HALAL PADA MASA PANDEMI COVID 19 DI INDONESIA - uswatun hasanah (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2021)
The Covid-19 pandemic destroyed the economic sector including the halal industry. This study focuses on analyzing the opportunities and challenges for the development of the halal industry in Indonesia. This research is descriptive research. Based on the results of the study, it was found that opportunities for the development of the sharia industry in Indonesia include the growing Muslim population, the opening of the e-commerce market for halal products, increased interest in purchasing halal products, the development of types of halal products is needed in order to balance market demand. Meanwhile, the challenges faced by the halal industry include the number of halal certificates that have not been maximal, the proliferation of imported products, economic uncertainty, and raw materials are still imported